2020
DOI: 10.1001/jamadermatol.2020.0036
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Comparison of Magnetic Resonance Imaging Findings and Clinical Assessment in Patients With Morphea

Abstract: scale) as reported by both physicians and patients, and the skin domains of both the Functional Assessment of Cancer Therapy-Bone Marrow Transplant (FACT-BMT; 0-4 scale for 47 items [maximum score, 188]) and Lee Symptom Scale (LSS; 0-4 scale for 5 categories [maximum score, 20]) as reported by patients. Results |The cohort consisted of 7 patients with NoGVHDP−, 9 with NoGVHDP+, 9 with ET, 8 with ST, and 13 with ET/ST. Clinical Severity Score responses were available for 34 patients (28 adult and 6 pediatric), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 7 publications
3
23
0
2
Order By: Relevance
“…In fact, studies have shown that MRI can reveal clinically occult musculoskeletal involvement (82)(83)(84), demonstrating subclinical extension of lesions beyond visible margins (41). MRI has also been shown to demonstrate active disease that would otherwise be misclassified as inactive based on using the LoSCAT alone (41). Given how crucial it is to accurately assess activity when managing morphea patients, this further underscores the utility of MRI in conjunction with clinical evaluation for deep morphea.…”
Section: Imaging Measures Of Morpheamentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, studies have shown that MRI can reveal clinically occult musculoskeletal involvement (82)(83)(84), demonstrating subclinical extension of lesions beyond visible margins (41). MRI has also been shown to demonstrate active disease that would otherwise be misclassified as inactive based on using the LoSCAT alone (41). Given how crucial it is to accurately assess activity when managing morphea patients, this further underscores the utility of MRI in conjunction with clinical evaluation for deep morphea.…”
Section: Imaging Measures Of Morpheamentioning
confidence: 99%
“…Deep morphea lesions often have very subtle surface changes, and palpation can be more important than visual inspection to appreciate the extent of these lesions. It also may be difficult to fully evaluate activity in these deeper lesions, and given that unchecked morphea activity can lead to permanent functional sequelae, patients with these deeper manifestations of morphea may benefit from MRI to determine disease activity and damage (40,41). Although involvement of joints and areas underlying areas of morphea is the most common presentation, patients may also experience sacroiliitis, generalized synovitis, and inflammatory arthritis.…”
Section: Extracutaneous Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scleroderma, or systemic sclerosis, is an autoimmune fibrosing disorder, consisting of two subsets: diffuse cutaneous systemic sclerosis (dSSc; a systemic disease characterized by widespread involvement of any organ system with a prevalence of 20/100,000 and peak incidence in females between 30 and 50 years old), and limited cutaneous systemic sclerosis (lcSSc; a disease characterized by manifestations of the CREST syndrome (calcinosis cutis, Raynaud phenomenon, esophageal dysmotility, sclerodactyly ( Figure 3 A), and telangiectasia). Cases without skin changes but other systemic manifestations have been reported as well and are described as systemic sclerosis sine scleroderma [ 22 , 23 , 24 ]. The skin is the main organ involved in scleroderma, and disease subsets are differentiated by the degree of skin involvement [ 23 ].…”
Section: Autoimmune/inflammatory Disorders and Vasculitidesmentioning
confidence: 99%